Clinical Decision Support Aiming to Accelerate Triage and Time to Dextrose-Containing IV Fluids in the ED for Children with Severe Metabolic Conditions - Kandaswamy, Swaminathan; Jain, Shabnam; Chambers, Dwight Diaz; Wilcox, William R.; Agha, Beesan S.; Dennis, Hailey; Brown, Sara P.; Orenstein, Evan W. (Applied Clinical Informatics, 2025)
This study aimed to describe human-centered design of clinical decision support (CDS) for children with metabolic diseases at high risk of rapid decompensation, assess the influence of CDS on care processes and patient outcomes, and share insights from the implementation.A CDS was designed in collaboration with pediatric genetics experts to provide accelerated triage and recommend dextrose-containing fluids for patients metabolic conditions. Formative usability testing was conducted with emergency department (ED) nurses and providers. Pre- and post-intervention data on triage, alert acceptance, and order set usage, as well as clinical outcomes such as time to dextrose fluids, intensive care unit (ICU) admission rates, and length of stay, were compared.Provider alert acceptance was at 39%. Following CDS implementation, nurse triage at Emergency Severity Index (ESI) <3 (ESI 1 or ESI 2 to escalate patients with metabolic conditions to a higher severity) increased from 84 to 98%. Time to dextrose-containing fluids from patient rooming to administration decreased significantly from 101 to 82 minutes (p = 0.006) for all patients with metabolic conditions, and from 110 to 88 minutes (p = 0.029) for those admitted to the hospital. However, the median time from arrival to fluids administration saw a non-significant reduction from 114 to 102 minutes (p = 0.07). ICU admission rates remained stable pre- and post-intervention (13% vs. 14%; p = 0.60), and there was no significant change in total length of stay.The CDS, developed through a user-centered design approach, improved appropriateness of triage acuity rates and reduced the time from rooming to administration of dextrose-containing fluids for children with metabolic diseases at risk of rapid decompensation. The study did not demonstrate a significant change in ICU admissions or length of stay, possibly due to increased patient load and external factors. The findings emphasize the importance of usability testing and clinician-centered design for effective CDS integration.
Keywords: clinical decision support; pediatrics; human-centered design; emergency department; pediatrics